Fillers, Mime and Self-Repetitions as Most Frequently Used Communication Strategies in Oral Expositions - Tabula, Rommel; Balagtas, Aris; Castillo, Myra Eugenia (JPAIR Multidisciplinary Research, 2014)
Achieving competence in an oral communication situation has always been the ultimate goal of both teacher and students in an ESL classroom. Long years of schooling and prolonged exposure to speech communication had empowered students’ speaking ability, but anxieties still emerge in their oral expositions. This exploratory study investigated the communication strategies of students in overcoming communication anxieties in their oral expositions. It also delved into the factors affecting their communication anxieties. Using Laurilla’s (2003) Categories of Communication Strategies, data were obtained from the 25 third year BS Tourism Management students of the Mariano Marcos State University, Philippines chosen through systematic random sampling. Transcriptions of their videotaped oral expositions were analyzed in terms of the frequency of occurrence of specific communication strategies. Interview was also utilized to support gathered quantitative data. Results revealed that the most common strategies of students in managing their communication anxieties during their oral expositions included fillers, mime, self-repetition, self-repair, and mumbling. It also disclosed that attitude toward language learning, motivation in learning the language, and socio-economic status are the factors that would affect communication anxieties.